Study of the yeast cytosolic Hsp70-system in protein homeostasis and life span regulation - Silver stained 2D-gels of protein extracts from wild type and Hsp70-mutant yeast strains - Öling, David; Andersson, Rebecca; Nyström, Thomas (University of Gothenburg, 2020)
Our study aims to answer the question "Which functions of the Hsp70 class of molecular chaperones are essential for yeast to maintain a standard replicative life span?". To answer this question, we utilised the disparate functions of the Hsp70's Ssa1 and 2 and their paralog Ssa4 in a yeast strain that lacks Ssa1/2 but has an ectopically increased production of Ssa4. We have gathered data on the behaviour of several different markers for protein aggregation under different circumstances, as well as data on proteins from other classes of molecular chaperones. The bulk of the data is in the form of multichannel microscopy images from widefield microscopy, with a few sets of western blots of protein extracts.

Images of two dimensional protein gels with protein extracts from wild type and Hsp70 mutant yeast strains in mid-exponential growth phase. The yeast were grown in rich medium (YP) with 2 % glucose as carbon source. The images have been aligned and the background has been removed.
The dataset was collected through imaging of two dimensional protein gels.
The image files are provided in TIFF format.

Vi har systematiskt studerat vilka funktioner hos de cytosoliska molekylära chaperonerna av klassen Hsp70 hos jäst som krävs för att upprätthålla en normal livslängd.

Bilder av tvådimensionella proteingeler med proteinextrakt från vildtyp och Hsp70-mutanta jäststammar i mitten av den exponentiella tillväxtfasen. Jästen har odlats i rikt medium (YP) med 2 % glukos som kolkälla.
Datasetet insamlades via fotografering av tvådimensionella proteingeler.
Bildfilerna är i TIFF-format.
Studier av det cytosoliska Hsp70-systemet från jäst och dess roll i proteinhomeostas och reglering av livslängd - Silverfärgade 2D-geler av proteinextrakt från vildtyp och Hsp70-mutanta jäststammar
Keywords: Cellular Senescence; Cellåldrande; Molecular Chaperones; Molekylära chaperoner; HSP70 Heat-Shock Proteins; HSP70-värmechockproteiner; Proteostasis Deficiencies; Proteostasbrist; Cell Biology; Cellbiologi; Microbiology; Mikrobiologi; Cell and Molecular Biology; Cell- och molekylärbiologi; Molecular Biology; Molekylärbiologi